Characteristics of ESD protection devices operated under elevated temperatures. (November 2016) - Liang, Wei; Dong, Aihua; Li, Hang; Miao, Meng; Kuo, Chung-Chen; Klebanov, Maxim; Liou, Juin J.
Abstract: In this paper, characteristics of electrostatic discharge (ESD) protection devices operating under ESD stress and various ambient temperatures are investigated. The devices considered are a P +/NW diode and several silicon controlled rectifiers (SCRs) including Lateral SCR (LSCR), Modified Lateral SCR (MLSCR), No Snapback SCR (NS-SCR), Low Voltage Triggering SCR (LVTSCR), and P-Substrate Triggered SCR (PSTSCR) fabricated in a 0.35 μm BCD (Bipolar-CMOS-DMOS) technology. Measurements are conducted using the Barth 4002 transmission line pulse (TLP) tester and the Signatone S1060 heating module, and the TLP I–V characteristics are analyzed in details. TCAD simulation is carried out and underlying physical mechanisms related to the effect of temperature on key ESD parameters are provided. Highlights: Characteristics of ESD devices under various temperatures are investigated. Some key ESD parameters under high temperatures are reported for the first time. TCAD simulation is carried out to offer physical insights.